KLASSEN TYPOLOGY-BASED EVALUATION OF FISCAL PERFORMANCE IN KUDUS REGENCY - Amanda, Yuanita; Agung Slamet Sukardi (Jurnal REP (Riset Ekonomi Pembangunan), 2025)
The purpose of this research is to see the level of independence, efficiency, effectiveness and growth in the Kudus Regency. The researcher chose Kudus Regency as the population. The sampling technique is saturated sampling. The realization report of the regional revenue and expenditure budget and the regional revenue target in Kudus Regency 2014-2024 is the population used as the research sample. This study uses a quantitative descriptive method. One of the instruments to assess the financial performance of the Regional Government is financial ratio analysis. The use of financial ratio analysis in public institutions is still very limited. Researchers are interested in conducting research from Kudus Regency. It can be concluded that the ratio of regional financial independence shows a very low value of financial independence and still depends on central transfer income, the effectiveness ratio is categorized as very effective where the local government has succeeded in achieving the designed regional income, and the efficiency ratio is classified as less efficient because the achievement of regional expenditure is higher than the achievement of revenue. Meanwhile, from Klassen's typology, it is concluded that one sector that makes the largest contribution to Kudus Regency is the processing industry. Local governments need to utilize revenue from existing revenue opportunities. For future researchers who conduct similar research, it is hoped that they will better master the financial performance of local governments.